2011
DOI: 10.4038/jnsfsr.v39i1.2923
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of noodles made from selected varieties of Sri Lankan rice with different physicochemical characteristics

Abstract: The physicochemical properties of eight popular Sri Lankan rice varieties (Bg 300, Bg 352, Bg 403, Bg 94-1, Ld 356, Bw 272-6b, At 405 and At 306) and the quality characteristics of noodles made from these varieties of rice were investigated. The physicochemical properties investigated were amylose content (AC), crude protein, fat content, starch properties and amylograph pasting properties. Rice noodles were prepared by gelatinization of dough made with rice flour followed by cold extrusion. Rice noodle sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 6 publications
4
30
1
Order By: Relevance
“…Likewise, Fari et al and Hormdok and Noomhorm found that the observed values for cooking time of rice noodle ranged from 5 to 9 min. The values for wheat‐based noodles are in agreement with the work of Ritthiruangdej et al , who obtained almost similar results (13.0–14.5 min) for WF noodle.…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…Likewise, Fari et al and Hormdok and Noomhorm found that the observed values for cooking time of rice noodle ranged from 5 to 9 min. The values for wheat‐based noodles are in agreement with the work of Ritthiruangdej et al , who obtained almost similar results (13.0–14.5 min) for WF noodle.…”
Section: Resultsmentioning
confidence: 90%
“…The water absorption index of noodles depends upon the proximate composition, gluten matrix and hydrogen bonding. Weak bonding and low protein content maximise the water absorption . Water absorption index mostly depends on the type and amount of starch granules .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations